Etika Guru Dalam Mendidik Siswa Yang Melakukan Pembullyan Di Lingkungan Sekolah - Fadilah, Sifa; Muhammad Rayhan Bambang Putra (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
This research examines the role of teachers in handling and preventing students from bullying behavior which often occurs in the school environment. This research was studied using descriptive qualitative methods by collecting data from various media and research documents. The subject of this research are teachers who always deal with students who behave bullying in the school environment. The analysis used in this research is data reduction, data presentation, and drawing conclusions. From the results of this analysis, there are 3 (three) forms of bullying that often occurs in the school environment, namely physical bullying, psychological bullying, and verbal bullying. In this case, the violence carried out took the form of hitting, kicking, and taunting. Here the role of the teacher in handling and preventing bullying behavior is by providing directions to students, providing coaching activities to students regarding bullying behavior, holding anti-bullying activities held at school. A teachers is not only an academic teacher in this research, the teachers must also be responsible for shaping students behavior and character.